Cardiopulmonary Resuscitation Capacity Building Training for High School Students in Martapura, Banjar Regency - Hammad, Hammad; Rizani, Khairir; Rachmadi, Agus; SPN, Endang; Rizani, Akhmad; Marwansyah, Marwansyah; Wilotono, Nasrullah (International Journal of Community Service Learning, 2023)
The Banjar Regency area is prone to flooding and is one of the disaster areas that can cause casualties and stress that triggers an increase in cardiovascular disease sufferers. This condition requires community preparedness for emergencies. The purpose of this community service activity is to train partners skills in cardiopulmonary resuscitation skills to be able to help victims of cardiac or respiratory arrest. The first implementation of this community service activity is carrying out an initial test to recognize emergency signs in heart and lung attacks, then providing an introduction to the concept of heart and lung emergency through lecture methods, discussion, and sharing related to real events of cardiopulmonary arrest in the community, then the final stage is evaluation of student abilities. The target of this community service activity was 40 students who are members of the High School Youth Red Cross in Martapura City, Banjar Regency. The results of this community service activity students understand material related to cardiopulmonary resuscitation, and providing basic life support counseling has a significant effect on student knowledge. Through this activity, students are expected to be able to provide a pre-hospital cardiopulmonary resuscitation simulation, and students can disseminate information to those closest to them.